Associations between tooth agenesis and displaced maxillary canines: a cross-sectional radiographic study - Chiaramonte, C. (Springer Berlin Heidelberg, 2018)
Background: The aim of present study was to test the association between hypodontia and displaced maxillary canine when compared with a control group. Methods: The study group was composed of 336 subjects with a mean age of 10.7 ± 1.2 years, presenting with at least one missing tooth. Exclusion criteria included syndromes, craniofacial malformations, extractions and trauma history and previous orthodontic treatment. The control group consisted of 336 subjects with a mean age of 10.7 ± 1.2 years, without agenesis. Stepwise multiple logistic regression using the backwards elimination and the Wald test method was performed to identify the best combination of hypodontia and displaced maxillary canine (P < 0.05). Results: The most represented category in study group consisted in mild agenesis (86.9%); moderate and severe agenesis groups respectively represented the 11.7 and 1.4% of study group. Agenesis was diagnosed in both arches in 46 subjects. Maxillary hypodontia and mandibular hypodontia was respectively detected in 156 and 134 subjects. The most frequent missing teeth were mandibular second premolars (45.8%), lateral incisors (41.7%) and maxillary second premolars (17.8%). A significant correlation between agenesis and displaced maxillary canine was observed in the study group (P < 0.05). Only the agenesis of maxillary lateral incisors remained in the final model during backward stepwise deletion. Significant association between the severity of dental agenesis and prevalence of displaced maxillary canine was not assessed. Conclusions: The outcomes revealed no difference related to the severity of dental agenesis and prevalence of displaced maxillary canine. Only the agenesis of maxillary lateral incisors should be considered directly connected with displaced maxillary canine. © 2018, The Author(s).